2013
DOI: 10.1530/joe-13-0393
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and glucose metabolism in men: current concepts and controversies

Abstract: A wealth of observational studies show that low testosterone is associated with insulin resistance and with an increased risk of diabetes and the metabolic syndrome. Experimental studies have identified potential mechanisms by which low testosterone may lead to insulin resistance. Visceral adipose tissue is an important intermediate in this relationship. Actions of testosterone or its metabolite oestradiol on other tissues such as muscle, liver, bone or the brain, and body composition-independent effects may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 118 publications
(163 reference statements)
5
92
0
3
Order By: Relevance
“…Unfortunately, no previous study has investigated the effect of testosterone therapy on cardiovascular morbidity or mortality, and therefore, the causality of the relationship between low testosterone levels and cardiovascular disease is unclear. Although observational studies show a consistent association of low testosterone with adverse lipid profiles [12,13], the question whether testosterone therapy exerts a beneficial effect plasma lipids remains uncertain. Moreover, in some studies, testosterone decreased circulating levels of HDL [14][15][16], considered to have a protective effect against coronary heart disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no previous study has investigated the effect of testosterone therapy on cardiovascular morbidity or mortality, and therefore, the causality of the relationship between low testosterone levels and cardiovascular disease is unclear. Although observational studies show a consistent association of low testosterone with adverse lipid profiles [12,13], the question whether testosterone therapy exerts a beneficial effect plasma lipids remains uncertain. Moreover, in some studies, testosterone decreased circulating levels of HDL [14][15][16], considered to have a protective effect against coronary heart disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…In human subjects, circulatory testosterone levels were negatively correlated with visceral obesity, IR, and fatty liver [911]. Similar observations were also reported in animal models [43] and testosterone replacement ameliorated MS symptoms [911]. El Hafidi et al reported low levels of testosterone in sucrose-fed rats for 20 weeks and no other study has noticed that in high-fructose-fed rats [44].…”
Section: Discussionmentioning
confidence: 58%
“…Clinical and animal studies reported the possible role of testosterone in the development of MS components including dyslipidemia, IR, and visceral obesity [911]. In human subjects, circulatory testosterone levels were negatively correlated with visceral obesity, IR, and fatty liver [911].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfavorable changes in the lipid profile (88), procoagulatory effects, activation of the sympathetic nervous system, and renin-angiotensin-aldosterone system, and insulin resistance are some of the indirect actions of testosterone that can affect the vasculature (25,52,66,76,105,119). Among the direct effects of testosterone, stimulation of proinflammatory enzymes in the vasculature [e.g., thromboxane synthase, as well as cyclooxygenase-1 (COX-1) and COX-2 in rat thoracic aorta and mesenteric arteries (31,177)], reactive oxygen species (ROS) generation in vascular smooth muscle cells (33), which may decrease NO bioavailability and lead to increased blood pressure and renal dysfunction (36,95,155,159), activation of vasoconstrictor signaling pathways (PKC, MAPKs), and increased vasoconstriction have been reported (34,35,99).…”
Section: Possible Mechanisms Responsible For Deleterious Effects Of Tmentioning
confidence: 99%